Non-linear analysis of laminated plates - Bich, Dao Huy (Vietnam Journal of Mechanics, 2002)
The governing equations of laminates plates taking into account the transverse shear deformation effects for large deformation are given. The formulation of Ritsz method and finite element method for non-linear analysis of this problem is presented